Prevalence of Hypersensitivity Reaction in Patients Attending Selected Diagnostic Centers NOVA/SOMLAB in Benadir Region, Somalia - Abdiaziz, Abdullahi Abdulkadir; Rahman, Md Ashiqur; Hossain, Md Biplob; Islam, Sadia; Rahaman, Shohanur; Chanda, Manashe; Mahbub, Afsana; Biswas, Tapos; Akram, Arifa (Bangladesh Journal of Infectious Diseases, 2023)
Background: The immune system plays a crucial role in maintaining health and protecting the human body against microbial invasions. Objective: The purpose of the present study was to assess the prevalence of hypersensitivities reaction in allergic patient attending selected diagnostic centers. Methodology: This cross- sectional was performed at selected hospitals. The study was carried out from 01st August 2023 to 30th November 2023 at the Immunology department of Nova Diagnostic and Research Institute, Somalia. There 300 samples were included in this study. Questionnaire and investigation (Sample Testing) was used as the main instrument for collecting patient socio-demographic profile and laboratory test were done at Nova diagnostic center. Results: A total 300 participants were enrolled in this study. Among the 300 the predominant the prevalence of respondents was high which was 273(91%) cases and most of the participants were Banana allergic which was 215 (71.7%) cases. Maximum cases were from age group of 2-20 years (48%) and followed by 21-39 years (22%), 40-58 years (17.67%) and >58 years (12.33%). There was a statistically significant correlation between allergic status and education (P=0.003), but not between allergic status and age group (P=00.219) or gender (P=0.456). Conclusion: The study revealed a significant correlation between allergic status and education, indicating that the majority of participants were allergic to bananas. Bangladesh Journal of Infectious Diseases, December 2023;10(2):85-91